Imamat am orang percaya dan relevansinya bagi pengembangan misi dalam konteks pluralisme di Indonesia - Nofia Hudaya (TE DEUM (Jurnal Teologi dan Pengembangan Pelayanan), 2021)
The Priesthood of All Believers is one of the main teachings of church reform in the Middle Ages, but unfortunately its implementation in the practice of congregational life is still often misunderstood or ignored. This paper aims to examine the nature and relevance of The Priesthood of All Believers as the foundation of mission for every believer, especially in the context of pluralism in Indonesia. The research method used is literature. At the end of this paper, it is found that every Christian must understand that whatever his profession in the secular world is a call from God to him, which must be seen as an exercise of his faith in God. In the context in Indonesia, every Christian is called to create harmony and peace in the midst of community. The laymen have a strategic role to carry out the inclusive mission to prevent the church from exclusivism.